Use of near-infrared spectroscopy in evaluating upper extremity muscle hemodynamics during an eight-hour exposure to repetitive hand-wrist motions - Maikala, Rammohan V.; Ciriello, Vincent M.; O'Brien, Niall V.; Banks, Jacob J.; Rivard, Amanda J. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/